A new iterative method for springback control based on theory analysis and displacement adjustment. (January 2016) - Zhang, Zengkun; Wu, Jianjun; Zhang, Shen; Wang, Mingzhi; Guo, Ruichao; Guo, Shaochang
Abstract: Springback is considered to be a manufacturing defect in sheet metal forming. When the tools are released after forming processes, the product will deviate from the desired shape due to its internal stresses. The deviation can be corrected by adjusting the tooling shape and/or optimizing the forming process. This paper will focus on tooling compensation (the forming process optimization is out of the discussion of this paper, although it is also an important method to control springback). Based on the displacement adjustment (DA) method, this paper will present a new iterative method for tooling compensation, which is a named sheet elements compensation (SEC) method. The aim of the SEC method is to overcome the difficulties, which are very common when using existing methods to solve springback problems. Three typical shapes are used to demonstrate the suitability and reliability of the SEC method. Additionally, a comparison between SEC method and existing methods is also implemented, which shows that the SEC method is also efficient in tooling design. Highlights: A new iterative method for tooling compensation (SEC method) is presented, which is effective and can overcome the difficulties in existing methods. Based on theory analysis, trials and errors and interpolation, a strategy for compensation factors evaluation is proposed. Three typical shape are used to demonstrate the reliability of the SEC method. Results show that SEC method possesses a remarkable convergence speed.